Stride regulation at the approach phase of long jump in visually impaired (F13) athletes - Theodorou, A.; Emmanouil, S.; Tasoulas, E.; Panteli, F.; Smirniotou, A.; Georgios, P. (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The present work studied whether visually impaired (VI) class F13 long jumpers showed at the approach run the same pattern of variability in footfall placement across trials as their non-VI counterparts. The long jump finalists (men and women), of the IBSA 2009 European Athletics Championship were recorded. VI long jumpers demonstrated an initial ascending variability followed by a descending one suggesting some type of regulation. This control emerged on the 5th and 4th stride prior to take-off and at a mean distance of 8.8±1.9m and 8.3±2.6m from the take-off board for men and women respectively. TBD variability reached a maximum value of 30.0±18.9cm and 25.2± 14.4cm and was finally reduced to 7.73cm (± 6.65cm) and 8.2± 2.6cm for males and females respectively. The striding pattern observed was similar to that reported in the literature for non-VI athletes.